C++ primer - Lippman, Stanley B.; Lajoie, Josee; Moo, Barbara E. (Upper Saddle River, NJ Addison-Wesley, 2013)
C++ Primer, Fifth Edition, introduces the C++ standard library from the outset, drawing on its common functions and facilities to help you write useful programs without first having to master every language detail. The book's many examples have been revised to use the new language features and demonstrate how to make the best use of them. This book is a proven tutorial for those new to C++, an authoritative discussion of core C++ concepts and techniques, and a valuable resource for experienced programmers, especially those eager to see C++ 11 enhancements illuminated.
Chapter 1-Getting Started -- Part 1-The Basics -- 1.2-Variables and Basic Types -- 1.3-Strings, Vectors, and Arrays -- 1.4-Expressions -- 1.5-Statements -- 1.6-Functions -- 1.7-Classes -- Part 2: The C++ Library -- 2.8-The IO Library -- 2.9-Sequential Containers -- 2.10-Generic algorithms -- 2.11-Associative Containers -- 2.12-Dynamic Memory -- Part 3: Tools for Class Authors -- 3.13-Copy Control -- 3.14-Overloaded Operations and Conversions -- 3.15-Object Oriented Programming -- 3.16-Templates and General Programming -- Part 4: Advanced Topics -- 4.17-Specialized Library Facilities -- 4.18-Tools for Large Programs -- 4.19-Specialized Tools and Techniques.
Includes index.
Keywords: C++ (Computer program language